Edukasi dan Praktik Pelvic Floor Muscle Training sebagai Upaya Pencegahan Gangguan Dasar Panggul pada Perempuan - Sari, Septi Ayu Arum Yuspita; Ratnasari, Ririn; Wijayanti, Aida Ratna; Salwa, Azzahra Desvania Rifda; Wulandari, Mila (Yayasan Inspirasi El Burhani, 2026)
Introduction: Pelvic Floor Muscle Training (PFMT) is an evidence-based intervention proven to strengthen pelvic floor muscles and prevent disorders such as urinary incontinence, pelvic organ prolapse, and sexual dysfunction in women. These conditions significantly affect quality of life, daily activities, and emotional well-being. Community health cadres play a critical role in health promotion, making capacity building on PFMT essential to support early prevention of pelvic floor disorders at the community level. Objective: This community service program aimed to improve the knowledge and practical skills of Aisyiyah cadres in Jambon Branch through structured education and hands-on PFMT practice as an effort to prevent pelvic floor disorders in women. Method: The program applied a participatory educational approach consisting of interactive lectures, group discussions, PFMT demonstrations, supervised practice sessions, and evaluation through pre- and post-tests. The activity was carried out in August 2025 and involved 22 eligible cadres, all women actively serving as community health volunteers and willing to participate fully in the training. Skill assessment was conducted through direct observation to evaluate the accuracy of pelvic floor muscle contraction techniques according to facilitator guidance. Result: The activity resulted in a significant increase in participants’ knowledge, with the average score rising from 40% on the pre-test to 80% on the post-test. Additionally, 80% of the cadres were able to perform correct pelvic floor muscle contractions after guided practice and individual correction. Participants expressed positive feedback, noting that the interactive methods facilitated better understanding and confidence in applying PFMT. Conclusion: The PFMT education and practice program effectively enhanced the knowledge and skills of Aisyiyah cadres within a single training session. This initiative demonstrates strong potential to serve as a sustainable community-based women’s health promotion strategy when followed by regular supervision and reinforcement.